Prevalência de síndrome metabólica em idosos - Haigert, Caroline Saraiva (Universidade do Vale do Rio dos Sinos, 2011)
Objective: To present an updated review and criticism on the Prevalence of Metabolic Syndrome (MS) in the Elderly. Methodology: We conducted a literature review study of its kind. References were collected from the PubMed database. This literature review was carried out studies and research with human subjects, published from 1997 to the present day, in English and Portuguese. The descriptors used were: Metabolic Syndrome X; Elderly, Prevalence, Metabolic Syndrome X; Elderly; Prevalence. Summary of the findings: By reading exploratory found 55 (fifty-five) articles involving Metabolic Syndrome in the Elderly. Were excluded by selective reading fifteen (15) articles. Among the articles selected, 10 (ten) were excluded by analytical reading, leaving thus 30 (thirty) articles for the study by reading interpretive. Conclusion: The data obtained in this literature review shows a high presence of risk factors that lead older people to be diagnosed with MS, the main are the following: increased waist circumference (84.3%) and hypertension (77.1%) which confirms the data and results available in literature, and reinforces the average result of 42.2% found in elderly patients with metabolic syndrome. These results indicate the need to form a hyaline change in the behavior of this population, focusing on a multidisciplinary approach.
Keywords: Síndrome X Metabólica; Idosos; Prevalência; Metabolic X Syndrome; Elderly; Prevalence